To determine which term will make System B equivalent to System A, we can manipulate the equations in System A.
The first equation in both systems is the same:
- \( 7x + 4y = -4 \)
We need to transform the second equation of System B into a form that matches System A. The second equation of System A is:
- \( 5x + 8y = 28 \)
We want to find a second equation in System B that corresponds to \( 5x + 8y = 28 \) after scaling or modification.
Notice that if we multiply the first equation \( 7x + 4y = -4 \) by 2, we get:
\[ 2(7x + 4y) = 2(-4) \] \[ 14x + 8y = -8 \]
This means that the equation \( -14x - 8y = 8 \) (which is just the negative of the new equation we've found) is equivalent to our original system.
Thus, the term that would make the systems equivalent is:
−14x−8y=8
So the correct response is:
−14x−8y=8